Karakteristik Limbah Cair Proses Produksi Kulit Sintetis dari Miselium Jamur: Wastewater Characteristics in the Synthetic Leather Production Process from Mushroom Mycelium - SAFIRA LAKSMI TRI OKTARANI; HISMIATY BAHUA; SRI PENI WIJAYANTI; NADIA RIZKI ARIYANI; NERISSA AZARINA RENALDY; IRA NURHAYATI DJAROT; NETTY WIDYASTUTI (Jurnal Teknologi Lingkungan, 2023)
ABSTRACT By carrying out an environmentally-friendly concept, a "biotech" startup company came up with an innovative synthetic leather derived from mushroom mycelium. The process of making synthetic leather produces various types of waste water. Unfortunately, there is no waste water treatment plant (WWTP) that treats the waste. Even though the raw materials are environmentally friendly, it might contain harmful materials. This study aimed to characterize the wastewater produced from the production process of synthetic leather that will be discharged directly into the environment. The process of making synthetic leather derived from mushroom mycelium produces wastewater from the washing process, boiling in the post-harvest process, and from the coloring process. Wastewater characteristic tests include several parameters including: pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solid (TDS), and oil and grease. The test results of raw water, washing water, boiled water, and wastewater samples were pH 7.44; 7.22; 9.18; 3.22. BOD 0.08 mg/l; 7.05 mg/l; 11.8 mg/l; 236 mg/l; COD <10 mg/l, 216 mg/l, 1,649 mg/l, 81.7 mg/l, TSS 21.0 mg/l; 35.0 mg/l; 152 mg/l; 962 mg/l, TDS 131.5 mg/l; 174.5 mg/l; 9,999 mg/l; 2,050 mg/l and oil & grease 2.00 mg/l; 4.00 mg/l. Based on the results of the analysis, several parameters have values above the wastewater quality standard. So, it is necessary to provide advice or solutions for "biotech" startup companies in treating wastewater that is indicated to be polluted. ABSTRAK Dengan mengusung konsep environmental-friendly, sebuah perusahaan rintisan biotech muncul dengan inovasi kulit sintetis yang berasal dari miselium jamur. Proses pembuatan kulit sintetis menghasilkan berbagai jenis air limbah. Hal ini disayangkan karena tidak adanya instalasi pengolahan air limbah (IPAL) yang mengolah hasil buangan limbah tersebut. Meskipun bahan material yang digunakan environmental-friendly, namun tidak menutup kemungkinan adanya kandungan yang membahayakan. Tujuan dari penelitian ini adalah untuk melakukan karakterisasi air limbah yang dihasilkan dari proses produksi kulit sintetis yang dibuang ke lingkungan secara langsung. Proses pembuatan kulit sintetis dari miselium jamur menghasilkan air limbah dari proses pencucian, perebusan pada proses pasca panen maupun dari proses pewarnaan. Uji karakteristik air limbah meliputi beberapa parameter: pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solid (TDS), dan oil & grease. Hasil pengujian sampel air baku, air cuci, air rebus, air limbah:  pH 7,44; 7,22; 9,18; 3,22. BOD 0,08 mg/l; 7,05 mg/l; 11,8 mg/l; 236 mg/; COD <10 mg/l, 216 mg/l, 1.649 mg/l, 81,7 mg/l, TSS 21,0 mg/l; 35,0 mg/l; 152 mg/l; 962 mg/l, TDS 131,5 mg/l; 174,5 mg/l; 9.999 mg/l; 2.050 mg/l dan oil & grease 2,00 mg/l; 4,00 mg/l. Berdasarkan hasil analisa, beberapa parameter mempunyai nilai di atas baku mutu air limbah. Karenanya, perlu adanya pemberian saran ataupun solusi kepada perusahaan rintisan biotech dalam pengolahan air limbah yang terindikasi tercemar.